ANALISIS STRATEGI PEMASARAN DI TENGAH PANDEMI COVID-19 UNTUK MENINGKATKAN OMZET PENJUALAN PADA RESTU BAKERY BOJONEGORO - Afrida Eva Erdiana; Siti Ning Farida (Universitas Halu Oleo, 2021)
This research uses Restu Bakery Bojonegoro as an object of research that sells various cakes and bakeries. The purpose of this study was to determine and analyze marketing strategies in increasing sales turnover during the Covid-19 pandemic at Restu Bakery Bojonegoro. The research method used is descriptive quantitative using SWOT, data collection techniques are carried out by means of observation, documentation, interviews and triangulation related to marketing strategies based on the 7P marketing mix indicators used by researchers in identifying strengths, weaknesses, opportunities and threats with the SWOT method. at Restu Bakery Bojonegoro.From this study, the results of the Internal Factor Analysis Summary showed a strength of 1.76 and a weakness of 1.46. Meanwhile, the results of the External Factor Analysis Summary show that the threat is 1.97 and the opportunity is 1.41. In this case, Restu Bakery Bojonegoro occupies the quadrant point I. In this case, a supporting marketing strategy is an aggressive strategy on the various opportunities and strengths of Restu Bakery Bojonegoro.